Papel social do jovem na unidade familiar: influência da experiência pedagógica da Casa Familiar Rural de Santa Maria das Barreiras - Pará - Brasil - SILVA, Maria Célia Vieira da (Universidade Federal do Pará, 2021)
This article analyze how the pedagogic experience of the familiar rural house (“CFR”) from Santa Maria das Barreiras-Pará influences the comprehention of the youth‟s role on the familiar peasants unities.Based on the qualitative aproach the research joins the speaches of the youths, parents, monitors and direction from the “CFR”, leaderships of the social and unions movements and assessors.The collective actors and the parents had different expectatives in relation to the function that the “CFR” should execute. On the side of the collective actors predominated an expectative for a forming of disseminators youth and militant youth.The expectatives of the most of the parents were stringly related with the strategies of the family for their recomposition, reproduction, empowering and protection of their members.The pedagogic experience reduced the afective and decision dependence from the youth in relation with their parents‟ opinion. That occurs in paralel with a more automny of circulation.In relation to the work on the familiar unity the changes on the agriculture practices were established speciallywhen the children and the parents were involved with the pedagogic dynamic of the “CFR”. On political and ideologic field the pedagogic experience allowed a dynamic of selfrecognyzing of the youth about their identity as farmers and a valorization of the rural area and of the parents‟ knowledge. The perspectives of the youth sometimes are articulated with the project of this study or with the project of the land. But these projects are shown incert because not all of them have condition to make them available.The analysis of the reports revealed that the particularity of the pedagogic experience of the “CFR” on the formation from the youth its the main tension point between the actors: the technic formation, either the social and policies one veiculated by the presence and orientation of the group.We identify signs of redimension of the youth‟s role which isn‟t only for they are inserted in the “CFR” but it is inserted in a dynamic of generational change